Dietary Incorporation of Ksheerabala Residue and Its Effect on Nutrient Utilisation, Growth Performance and Blood Biochemical Parameters in Crossbred Calves - Rani, K. Jasmine; Ally, K.; Seethal, C.R. Chithrima; Bunglavan, Surej Joseph; Gangadevi, P.; Shyama, K. (Indian Journal of Animal Nutrition, 2018)
Twelve healthy crossbred calves of one month age were divided into two groups of six each based on age, sex and body weight to study the effect of inclusion of ksheerabala residue in the diet on their growth, nutrient digestibility and blood biochemical profile. The animals in treatment T1 (control) were given standardconcentrate mixture as per ICAR (2013) while in group T2 ksheerabala residue was included to the level of 40%. The DM intake, growth, haematological and biochemical parameters were found to be similar in both the groups. Hence, Ksheerabala residue could be included in the calf ration up to 40% level without any adverse effect on nutrient digestibility and growth performance.